THE DEVELOPMENT OF NEIGHBOR LAW IN INDONESIA - Amalia, Rizky; Agustin, Erni; Sabrie, Hilda Yunita; Adhami, Latifatur Rokhmah; Sophia, Nada (Jurnal Bina Mulia Hukum, 2023)
Neighbor law was born in the midst of community life to regulate and limit rights and obligations in neighborly relationships. One of the developments in neighbor law is the concept of servitude or property easement. Issues related to servitude right in Indonesia are still frequently encountered, often resulting in illegal actions that lead to losses for others. Therefore, based on several court decisions in Indonesia, it is necessary to conduct an in-depth study of property easements as a limitation on property rights and legal protection for those who are harmed in cases involving property rights restrictions. This research is a legal study that employs three approaches: legislative approach, conceptual approach, and case approach. The results reveal that servitude right is a restriction on property rights over land that is still applicable according to civil law provisions and is based on the social function found in agrarian law. Legal protection provided through the judicial system in Indonesia regarding cases involving property rights restrictions and violations of servitude right involves filing lawsuits by the injured party based on illegal actions. If it is proven that the defendant has committed an illegal act, the judge will issue a court order (aanmaning) to perform or cease a certain action, as well as award compensation to the harmed party for actions that violate the servitude right.